Customer complaints and organizational responses: The effects of complainants' perceptions of justice on satisfaction and loyalty - Karatepe, Osman M. (My University, 2006)
This study investigates: (i) the effects of various organizational responses to complaints on distributive, procedural, and interactional justice; and (ii) the effects of complainants' perceptions of distributive, procedural, and interactional justice on satisfaction and loyalty. This study is conducted on a sample of Turkish guests in Northern Cyprus hotels. The hypothesized relationships are tested using LISREL 8.30 through path analysis. Path analysis demonstrates that atonement is an organizational response to customer complaints associated with distributive justice, and facilitation and promptness have significant positive effects on procedural justice. Promptness appears to have a stronger effect on procedural justice than that of facilitation. In addition, path analysis reveals that apology, explanation, attentiveness, and effort are the four organizational response dimensions influencing interactional justice. Of the four organizational response options, attentiveness and effort have the largest effects on interactional justice. Path analysis shows that all justice dimensions exert significant positive effects on complainant satisfaction and loyalty. Of the three justice dimensions, the effect of interactional justice on complainant satisfaction and loyalty is stronger than those of distributive and procedural justice. Discussions of the results, implications for hotel managers, and avenues for future research are presented in the study. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Complainant loyalty; Complainant satisfaction; Distributive justice; Interactional justice; Northern Cyprus; Procedural justice